Propagation of Ultralow‐Frequency Waves from the Ion Foreshock into the Magnetosphere During the Passage of a Magnetic Cloud. Issue 2 (28th January 2021) - Takahashi, Kazue; Turc, Lucile; Kilpua, Emilia; Takahashi, Naoko; Dimmock, Andrew; Kajdic, Primoz; Palmroth, Minna; Pfau‐Kempf, Yann; Soucek, Jan; Motoba, Tetsuo; Hartinger, Michael D.; Artemyev, Anton; et al.
Abstract: We have examined the properties of ultralow‐frequency (ULF) waves in space (the ion foreshock, magnetosheath, and magnetosphere) and at dayside magnetometer stations ( L  = 1.6–6.5) during Earth's encounter with a magnetic cloud in the solar wind, which is characterized by magnetic fields with large magnitudes (∼14 nT) and small cone angles (∼30°). In the foreshock, waves were excited at ∼90 m Hz as expected from theory, but there were oscillations at other frequencies as well. Oscillations near 90 mHz were detected at the other locations in space, but they were not in general the most dominant oscillations. On the ground, pulsations in the approximate Pc2–Pc4 band (5 mHz–120 mHz) were continuously detected at all stations, with no outstanding spectral peaks near 90 mHz in the H component except at stations where the frequency of the third harmonic of standing Alfvén waves had this frequency. The fundamental toroidal wave frequency was below 90 mHz at all stations. In the D component spectra, a minor spectral peak is found near 90 mHz at stations located at L  < 3, and the power dropped abruptly above this frequency. Magnetospheric compressional wave power was much weaker on the nightside. A hybrid‐Vlasov simulation indicates that foreshock ULF waves have short spatial scale lengths and waves transmitted into the magnetosphere are strongly attenuated away from noon. Key Points: A magnetic cloud produces an ion foreshock populated with ultralow frequency (ULF) waves with higher frequencies and wider spectral widths than usual In the magnetosphere and on the ground, ULF waves are detected in a wide frequency range of ∼5 mHz–120 mHz Numerical simulation indicates short spatial scales, as well as multiple frequencies, of the foreshock waves